1988
DOI: 10.1200/jco.1988.6.11.1753
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial correlates of cancer survival: a subsequent report 3 to 8 years after cancer diagnosis.

Abstract: Professional and public interest in possible relationships between psychosocial factors and disease outcome continues to increase. Published research in this area, however, is marked by contradictory results. Positive relationships between a variety of psychosocial factors and length of survival from cancer are reported, but other studies uncover no such associations. In a previously reported prospective investigation of 359 patients with newly diagnosed malignant diseases, we found no relationship between cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(58 citation statements)
references
References 15 publications
3
54
1
Order By: Relevance
“…This could not be confirmed in another study (Cassileth et a/., 1988). Similarly, the initial findings on the effects of adverse life events on relapse of breast cancer (Ramirez et al, 1989) have not been supported by subsequent research (Barraclough et al, 1992).…”
Section: Specific Explanatory Factorscontrasting
confidence: 40%
“…This could not be confirmed in another study (Cassileth et a/., 1988). Similarly, the initial findings on the effects of adverse life events on relapse of breast cancer (Ramirez et al, 1989) have not been supported by subsequent research (Barraclough et al, 1992).…”
Section: Specific Explanatory Factorscontrasting
confidence: 40%
“…Instead, it has been suggested that clinical features such as performance status and the presence of certain symptoms may give a better idea of prognosis (Cassileth et al, 1988;Reuben et al, 1988). For instance, Reuben et al (1988) found that the predictive power of the Karnofsky Index was improved when combined with five symptoms (shortness of breath, problems eating or loss of appetite, trouble swallowing, dry mouth and weight loss) which had independent predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from previous studies suggest that knowledge of the patient's sex, age, primary tumour type or site of metastases may contribute little to the prediction of survival times (Reuben et al, 1988) and that the same is true for psychological factors such as feelings of hopelessness, life satisfaction and the amount of adjustment needed in response to initial diagnosis (Cassileth et al, 1988). Instead, it has been suggested that clinical features such as performance status and the presence of certain symptoms may give a better idea of prognosis (Cassileth et al, 1988;Reuben et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Although many community resources and family members can serve important caregiving roles, the presence of a dedicated spouse may be the most important component of strong social support. Not surprisingly, therefore, most studies have supported the hypothesis that all-cause mortality, cancer-specific mortality, and quality of life are better in married than unmarried cancer patients across many different tumor types, [15][16][17][18][19][20][21][22][23] including primary brain tumors. [24][25][26] This information is important for counseling patients, marshalling resources, and designing clinical trials.…”
Section: Discussionmentioning
confidence: 99%